Measurement of isolated photon production in deep inelastic ep scattering ZEUS collaboration - Chekanov, S.; Derrick, M.; Magill, S.; Musgrave, B.; Nicholass, D.; Repond, J.; Yoshida, R.; Mattingly, M.C.K.; Antonioli, P.; Bari, G.; Bellagamba, L.; Boscherini, D.; et al. (Elsevier, 2010)
Isolated photon production in deep inelastic ep scattering has been measured with the ZEUS detector at HERA using an integrated luminosity of 320 pb(-1). Measurements were made in the isolated-photon transverse-energy and pseudorapidity ranges 4 < E(T)(gamma) < 15 GeV and 0.7 < eta(gamma) < 0.9 for exchanged photon virtualities, Q(2), in the range 10 < Q(2) < 350 GeV(2) and for invariant masses of the hadronic system W(X) > 5 GeV. Differential cross sections are presented for inclusive isolated photon production as functions of Q(2), x, E(T)(gamma) and eta(gamma). Leading-logarithm parton-shower Monte Carlo simulations and perturbative QCD predictions give a reasonable description of the data over most of the kinematic range. (C) 2010 Elsevier B.V. All rights reserved.